Biomechanical evaluation of the relationship between postural control and body mass index - Ku, Pei Xuan (Elsevier, 2012)
Postural stability is crucial in maintaining body balance during quiet standing, locomotion, and any activities that require a high degree of balance performance, such as participating in sports and dancing. Research has shown that there is a relationship between stability and body mass. The aims of this study were to examine the impact that two variables had on static postural control: body mass index (BMI) and gender. Eighty healthy young adults (age=21.7±1.8. yr; height=1.65±0.09. m; mass=67.5±19.0. kg) participated in the study and the static postural control was assessed using the Biodex Balance System, with a 20. Hz sampling rate in the bipedic stance (BLS) and unipedic stance (ULS) for 30. s. Five test evaluations were performed for each balance test. Postural control was found to be negatively correlated with increased adiposity, as the obese BMI group performed significantly poorer than the underweight, normal weight and overweight groups during BLS and ULS tests. The underweight, normal weight and overweight groups exhibited greater anterior-posterior stability in postural control during quiet stance. In addition, female displayed a trend of having a greater postural sway than male young adults, although it was evidenced in only some BMI groups. This study revealed that BMI do have an impact on postural control during both BLS and ULS. As such, BMI and gender-specific effects should be taken into consideration when selecting individuals for different types of sporting activities, especially those that require quiet standing.